A systematic validation of hot Neptunes in TESS data. Issue 1 (22nd November 2022) - Magliano, Christian; Covone, Giovanni; Dobal, Richa; Cacciapuoti, Luca; Tonietti, Luca; Giacalone, Steven; Vines, Jose I; Inno, Laura; Jenkins, James S; Lissauer, Jack J; Bieryla, Allyson; Oliva, Fabrizio; et al.
ABSTRACT: We statistically validated a sample of hot Neptune candidates applying a two-step vetting technique using dave and triceratops . We performed a systematic validation of 250 transit-like events in the Transiting Exoplanet Survey Satellite archive in the parameter region defined by P4 d and 3 R_R 5 R_ . Through our analysis, we identified 18 hot Neptune-sized candidates, with a false positive probability 50 per cent . Nine of these planet candidates still need to be confirmed. For each of the nine targets, we retrieved the stellar parameters using ARIADNE and derived constraints on the planetary parameters by fitting the light curves with the juliet package. Within this sample of nine candidates, we statistically validated (i.e. with false positive probability 0.3 per cent ) two systems (TOI-277 b and TOI-1288 b) by re-processing the candidates with triceratops along with follow-up observations. These new validated exoplanets expand the known hot Neptunes population and are high-priority targets for future radial velocities follow-up.